KEPUTUSAN MAHASISWA ANGKATAN 2013/2014 DALAM MEMILIH FAKULTAS EKONOMI UNIVERSITAS BATANGHARI - Hasminidiarty Hasminidiarty (Jurnal Ilmiah Universitas Batanghari Jambi, 2014)
Higher Education is a quality university that is able to carry out his duty to improve the quality, roles and responsibilities in education so that universities not only is the container for the print title only undergraduate, but a container to produce graduates who are able to master and apply the disciplines acquired. In essence University of Batanghari was established to develop and nurture science and technology as well as a part of the body in an attempt to complete the formation of the Indonesian people, because it is a system of education tailored to the real needs of the development of Indonesia. The question is how much influence the product, price, place, promotion set by the University of Batanghari the student's decision in choosing the University of Batang, and where the factor of the variable product, price, place and promotion are the most influencing prospective students choose Faculty of Economics, University of Batanghari.The study results revealed that the pricing strategy for the product, price, place and promotion that has been established by the University of Batang greatly affect the prospective student choose the Faculty of Economics and when examined separately, the biggest variable affecting the decision of selecting students of the Faculty of Economics is a variable product, then other variables influence is a variable and variable promotion. As for the price variable is not significant to the decision of the students chose Faculty of Economics University of Batanghari.Keywords: product, price, place, promotion